IDENTIFIKASI SALMONELLA TYPHI PADA PENDERITA DEMAM TIFOID DI PUSKESMAS MALILI - Ny. Marhani (Voice of Midwifery, 2018)
The success of epidemiological survey of Salmonella is associated with procedures adopted to differentiate the genotypes of Salmonella typhi. The research aimed identification of Salmonella typhi from the blood culture of typhoid fever suspect.The research was conducted in the Microbiology Laboratory, Faculty of Medicine,  Hasanuddin University. Samples were taken from  Public health centers (PHC) in Malili. This was an analytic quantitative research with the cross sectional approach. Samples were collected from the blood of the patients with suspected  positive typhoid fever suspects. The  samples were cultured to obtain  S.typhi isolates finally the data were analysed.The research result indicates that in the culture examination, the isolation result of the Salmonella typhi from the blood samples of 98 patients, its obtained 20 (20.4%) positive typhoid fever samples. This show that successfull identification of Salmonella typhi still lower. This is depend of several factor such as using antibiotic before take of blood, limited used of isolation media, total of  less bacteria in blood, less volume of blood and time to take of blood not exactly.Keywords : Salmonella typhi,isolation, typhoid fever